2022
DOI: 10.1038/s41467-022-28687-w
|View full text |Cite
|
Sign up to set email alerts
|

Chemical medium-range order in a medium-entropy alloy

Abstract: High-/medium-entropy alloys (H/MEA) have the inherent local chemical order. Yet, as a structural link between the incipient short-range order and mature long-range counterpart, the chemical medium-range order (CMRO) is conjectural and remains open questions as to if, and what kind of, CMRO would be produced and if CMRO is mechanically stable during plastic deformation. Here, we show compelling evidences for CMRO in an Al9.5CrCoNi MEA. Specifically, the electron diffraction under both [$$112$$ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…In contrast with the MSROs the distribution of CSROs is highly irregular throughout the individual grain. This was demonstrated by computational studies 14,15,22,26 and experimental images [16][17][18][19][20][21]33,34 .…”
Section: Underlying Deformation Mechanismmentioning
confidence: 78%
See 4 more Smart Citations
“…In contrast with the MSROs the distribution of CSROs is highly irregular throughout the individual grain. This was demonstrated by computational studies 14,15,22,26 and experimental images [16][17][18][19][20][21]33,34 .…”
Section: Underlying Deformation Mechanismmentioning
confidence: 78%
“…However, to determine which MSRO motif exists in the realdeformation structure, further TEM-energy dispersive spectroscopy characterisation 17,18 is required. CSRO in a few MPEAs can be described in terms of 'preference for unlike species and avoidance of like pairs' 17,18,21,39 . Our MC simulations revealed that lowering the temperature of the Fe 40 Mn 40 Cr 10 Co 10 structure led to a relatively strong tendency for Fe-Co, Mn-Cr, Mn-Co, Fe-Mn, and Fe-Cr, promoting the variability of atomic packing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations